Phraseologisierte Partizipialkonstruktionen im Deutschen und Polnischen - Schatte, Czesława (Studia Germanica Posnaniensia, 2018)
The author analyses participial constructions in German and Polish taking into consideration their semantic aspect as well as pragmatic one and discusses their specific status on the borderline between syntax and phraseology.